1985
DOI: 10.1073/pnas.82.3.765
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the mouse serum albumin gene introduced into differentiated and dedifferentiated rat hepatoma cells.

Abstract: A 23-kilobase-pair segment of DNA containing the entire mouse serum albumin gene as well as 2.2 kilobase pairs of 5' and 4.3 kilobase pairs of 3' flanking sequences has been introduced into pSV2dhfr, a plasmid in which expression of the mouse dihydrofolate reductase cDNA is under the control of simian virus 40 sequences. This vector, pSV2dhfr-alb, was used to transfect differentiated and variant dedifferentiated rat hepatoma cells. Nine independent clones of transfected differentiated cells secrete considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Introduction into cultured cells of cloned genes encoding for tissue-specific functions results in preferential expression in the appropriate cell types [5,8,20,351. The mouse albumin gene is specifically expressed in stably transfected differentiated rat hepatoma clones, while in transfected dedifferentiated variants the level of expression is significantly lower [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Introduction into cultured cells of cloned genes encoding for tissue-specific functions results in preferential expression in the appropriate cell types [5,8,20,351. The mouse albumin gene is specifically expressed in stably transfected differentiated rat hepatoma clones, while in transfected dedifferentiated variants the level of expression is significantly lower [8].…”
Section: Introductionmentioning
confidence: 99%
“…Introduction into cultured cells of cloned genes encoding for tissue-specific functions results in preferential expression in the appropriate cell types [5,8,20,351. The mouse albumin gene is specifically expressed in stably transfected differentiated rat hepatoma clones, while in transfected dedifferentiated variants the level of expression is significantly lower [8]. Analysis of gene-specific expression performed in short-term transfection experiments has shown that DNA sequences a few ten or hundred nucleotides in length are instrumental in enhancement of expression in differentiated cells of specific lineages [9, 11, 18, 421. In the case of the rat albumin gene, the immediate 5'-flanking region of the gene fused to the chloramphenicol acetyltrans$erase (CAT) gene specifically elicits high CAT activity in transfected hepatoma cells [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to those that transform nonmalignant cells [23,31], the successful transfer of genes that specify specific proteins [7,10], and alter the hormonal responsiveness of neoplastic cells [19,28], has been accomplished. The transfer and expression of genes specifying membrane-associated proteins was achieved as well, indicating that complex intracellular processing mechanisms could be applied by the recipient cells to express the products of exogenous DNAs [9,18].…”
Section: Discussionmentioning
confidence: 99%
“…However, additional sequences may be required for transcriptional control during development, since an enhancer located at -10 kilobases (kb) from the cap site is essential for high-level expression of the albumin gene in transgenic mice (40). Comparison of the rodent albumin 5'-flanking sequences with the human counterpart demonstrates more than 90%o sequence conservation up to position -250, indicating that these promoter sequences are recognized by evolutionarily conserved proteins (7,13). The characterized DNA-binding proteins interacting with these cis-acting sequences in the rat albumin promoter (2, 7) and in the mouse promoter (28, 29) include the liver-specific LF-Bl/HNF1 (1Sa) and C/EBP (26), and the ubiquitous CTF/NF1 (39, 45) and NFY (43).…”
mentioning
confidence: 99%